[18F]-sodium fluoride PET/CT is an imaging-derived biomarker of hydroxyapatite expression in carotid plaque: sub-study of the Canadian Atherosclerosis Imaging Network (CAIN-2). (3rd June 2015) - Cocker, MS; Spence, J; Hammond, R; Wells, GA; Mc Ardle, B; deKemp, RA; Lum, C; Adeeko, A; Khan, A; Alturkustani, M; Hammond, L; Hill, A; et al.
Abstract : Background: It has been hypothesized that [18F]-sodium fluoride (NaF) uptake imaged with positron emission tomography (PET) binds to hydroxyapatite molecules expressed in regions with active calcification. Therefore, we aimed to validate NaF as a marker of hydroxyapatite expression in high-risk carotid plaque. Methods: Eleven patients (69 ± 5 years, 3 female) scheduled for carotid endarterectomy were prospectively recruited for NaF PET/CT. One patient received a second contralateral endarterectomy; two patients were excluded (intolerance to contrast media and PET/CT misalignment). The bifurcation of the common carotid was used as the reference point; NaF uptake (tissue to blood ratio - TBR) was measured at every PET slice extending 2 cm above and below the bifurcation. Excised plaque was immunostained with Goldner's Trichrome and whole-slide digitized images were used to quantify hydroxyapatite expression. Pathology was co-registered with PET. Results: NaF uptake was related to the extent of hydroxyapatite expression (r=0.45, p<0.001). Upon classifying bilateral plaque for symptomatology, symptomatic plaque was associated with cerebrovascular events (3.75±1.1 TBR, n=9) and had greater NaF uptake than clinically silent asymptomatic plaque (2.79±0.6 TBR, n=11) (p=0.04). Conclusion: NaF uptake is related to hydroxyapatite expression and is increased in plaque associated with cerebrovascular events. NaF may serve as a novel biomarker of active calcification and plaque vulnerability.